Community Empowerment In Monitoring Children's Growth Through Health Education About Prelacteal Feeding At The Public Health Center The Region Of Surabaya City Health Office - Kharisma Kusumaningtyas; Dwi Wahyu Wulan Sulistyowati; Titi Maharrani (Peneliti Teknologi Teknik Indonesia, 2023)
Some of the diseases which can be the biggest causes of infant mortality are diarrhea, tetanus, perinatal disorders, and inflammation of the lower respiratory tract (Hapsari, 2004 in Hidayat, 2009). To reduce neonatal morbidity and mortality and to achieve SDGs, can be carried out by early initiation of breastfeeding (IMD), giving colostrum in the early period after birth and continuing with exclusive breastfeeding of infants from birth until the age of 6 months (Walia, et.al, 2009). The purpose of this activity is to participate in efforts to improve infant health services through exclusive breastfeeding and prelacteal feeding at the Jagir Public Health Center, Surabaya City Health Office. Implementation date is 29-30 September 2021. The method of activity is to carry out Health Education in the form of counseling about exclusive breastfeeding, counseling about prelacteal feeding, formation of exclusive breastfeeding awareness groups. The results of prelacteal feeding counseling activities as an effort to optimize child development can increase the knowledge of participants by 77.5%. This happened because the mother can understands the knowledge about Exclusive Breastfeeding and Prelacteal Feeding so that the mother is committed to giving Exclusive Breastfeeding only without giving Prelacteal Feeding Food to her child. The Community Service Activities can form ASI Awareness Groups in each Neighborhood Association area which chaired by one Cadre. The Public Health Center can monitor the activities of the ASI awareness group every month. Collaborating with the Neighborhood Association administrator of each group for all of the activities related to exclusive breastfeeding.